Answer: Angie = 6, Jemma = 18
<u>Step-by-step explanation:</u>
Let x represent the current age of Angie
Current Age Age 5 years from now
Angie: x x + 5
Jemma: 3x 3x + 5
5 years from now the sum of their ages is 34
(x + 5) + (3x + 5) = 34
4x + 10 = 34
4x = 24
x = 6
Angle's current age is x = 6
Jemma's current age is 3x = 3(6) = 18
Answer:
5/-1
Step-by-step explanation:
y1-y2/x1-x2
9+3x^2
It's technically already in simplest form, except you usually put x first
=3x^2+9
To solve this equation by elimination, what you would do is multiply one of the equations by -1, or distribute -1 to each term in the equation, any of the 2 equations. Then align the equations and add them together.
-(X + 3y = 3)
-X - 3y = -3
-X - 3y = -3
X + 6y = 3
__________
3y = 0
y = 0/3 = 0.
Now we can solve for x, by simply plugging the value of y into any of the 2 equations.
X + 6y = 3
X + 6(0) = 3
X + 0 = 3
X = 3.
The solution to your system of equations would be (3,0).
Check this by plugging in the point to the other equation and see if it is true.
X + 3y = 3
(3) + 3(0) = 3
3 + 0 = 3
3 = 3.
Thus it is the solution.